Plastics Materials - Brydson, J. A. (Butterworth-Heinemann, 1999)
The seventh edition of this classic reference work once more provides a comprehensive overview of commercially available plastics materials. Bridging the gap between theory and practice, it enables scientists to understand the commercial implications of their work as well as providing technologists with a theoretical background. Since the previous edition, several new materials have been announced. Many of these materials result from metallocene catalyst technology. In addition, developments also continue with condensation polymers with several new polyester type materials of interest for bottle-blowing and/or degradable plastics. New phenolic-type resins have also been announced. As with previous editions, an explanation of the properties of these new materials in terms of their structure and morphology involving the principles laid down in the earlier chapters is presented.